Fullerene derivatives as dual inhibitors of HIV-1 reverse transcriptase and protease. (1st January 2021) - Yasuno, Takumi; Ohe, Tomoyuki; Kataoka, Hiroki; Hashimoto, Kosho; Ishikawa, Yumiko; Furukawa, Keigo; Tateishi, Yasuhiro; Kobayashi, Toi; Takahashi, Kyoko; Nakamura, Shigeo; Mashino, Tadahiko
Graphical abstract: Abstract: In the present study, we newly synthesized three types of novel fullerene derivatives: pyridinium-type derivatives trans -3a and 4a -5b, piperidinium-type derivative 9, and proline-type derivatives 10a -12 . Among the assessed compounds, 5a, 10e, 10f, 10i, 11a -d, and 12 were found to inhibit both HIV reverse transcriptase and HIV protease (HIV-PR), with IC50 values in the low micromolar range being observed. Regarding HIV-PR inhibition activity, proline-type derivatives 11a -11d and 12, bearing an alkyl chain between the hydroxylmethylcarbonyl (HMC) moiety and pyrrolidine ring, were more potent than other derivatives. This result might indicate that connecting HMC moieties with proline-type fullerene derivatives through properly sized alkyl chain leads to improved HIV-PR inhibitory activity.